Efficiency and risk in european banking - Franco Fiordelisi; David Marqués-Ibá\~nez; Phil Molyneux (European Central Bank (ECB), 2010)
We analyze the impact of efficiency on bank risk. We also consider whether bank capital has an effect on this relationship. We model the inter-temporal relationships among efficiency, capital and risk for a large sample of commercial banks operating in the European Union. We find that reductions in cost and revenue efficiencies increase banks' future risks thus supporting the bad management and efficiency version of the moral hazard hypotheses. In contrast, bank efficiency improvements contribute to shore up bank capital levels. Our findings suggest that banks lagging behind in their efficiency levels might expect higher risk and subdued capital positions in the near future.
Keywords: G21; D24; C23; E44; 330; banking risk; capital; Efficiency; Bankrisiko; Rentabilität; Bank; Eigenkapital; Panel; Kausalanalyse; EU-Staaten